Cumulative interpersonal relationship risk and resilience models for bullying victimization and depression in adolescents. (1st March 2020) - Zhao, Yongping; Zhao, Yufang; Lee, Yueh-Ting; Chen, Li
Highlights: CIRR significantly positively predicted SBV and depression. CIRR could directly decrease resilience and increase SBV and depression. CIRR could indirectly decrease resilience by SBV and increase depression. CIRR linear models for SBV and depression were constructed. Two mediation models of resilience in the relationships among CIRR, SBV and depression were constructed. Abstract: Studies have documented that school bullying victimization (SBV) triggered by interpersonal relationship risks (IRRs) can increase depression. However, the predictive patterns of cumulative IRRs (CIRR; classmate, parent-child, teacher-student, and friend relationships risks) on SBV and depression and its psychological mechanism remain unclear from a positive psychological perspective. This study explored CIRR models for SBV and depression and tested two mediation models of resilience in relationships among CIRR, SBV and depression. Self-report questionnaires were answered by 742 valid participants between 11 and 19 years of age. Findings showed that CIRR significantly predicted SBV and depression, with a proportionate increase in SBV and depression as the CIRR increased. Furthermore, the results confirmed the two mediation hypotheses. CIRR could directly decrease one's resilience and, therefore, increase one's SBV and level of depression. CIRR could also indirectly decrease one's resilience by SBV and further increase one's level of depression. The results construct CIRR linear model for SBV and depression and mediation models of resilience among CIRR, SBV and depression. Our results indicate that, to decrease SBV and depression based on multiple IRRs exposures, comprehensive intervening in four IRRs from a psychopathological perspective or cultivating resilience in adolescents from a positive psychological perspective is required.